Evaluation of the Surgical Tray Opening Procedure in Operating Suites: Systematic Review and Recommendations - Bussières, Martin; L’Espérance, Sylvain; Coulombe, Martin; Rhainds, Marc (Operating Room Nurses Association of Canada Journal, 2017)
Introduction: Optimizing the processes involved in managing operating suite activities is an essential element in obtaining gains in efficiency. The early opening of surgical trays could represent an innovative practice for reducing operating times and wait periods between surgeries as well as for increasing the number of daily surgeries. The purpose of this systematic review is to assess the risks and benefits of introducing this practice in the operating room. Methodology: A systematic literature review was conducted in various indexed databases as well as in the grey literature in order to identify synthesis studies, clinical guidelines and randomized and non-randomized studies on the impact of opening surgical trays early. The following indicators were sought: time lapse between the patient’s entrance and the beginning of surgery, the frequency of surgical tray contamination, and the rate of surgical wound infection. Results: An original study and four practice guides were included after a quality assessment. No studies on efficiency gains associated with the early opening of surgical trays were found. The results of the experimental study suggest that the contamination rate for uncovered surgical trays is low for the first 30 minutes (4%) and increases over time with exposure to the ambient air. Most clinical guidelines recommend preparing the surgical instruments as close to the beginning of surgery as possible without specifying the minimum time interval to be respected as well as whether or not the patient is in the operating room. Discussion: The analysis of all the available data does not make it possible to determine the optimal moment for opening the surgical trays. Given the uncertainty regarding the risks of infection, and the lack of data on the associated benefits, the decision to opt for a change in practice in the opening of surgical trays should be based on a range of factors. An assessment of the data therefore suggests caution and that a feasibility analysis, including a review of all processes and parameters for managing the risks associated with the early opening of surgical trays, be conducted before initiating any changes in the institutions where a change of practice is being sought.